CERTAIN ASPECTS OF HIGH LEVEL RADIOACTIVE WASTES – A BRIEF NOTE ON THE PROBLEM - Rana, M. A. (The Nucleus, 2020)
Issues of high level nuclear waste disposal which involve a number of known and unknown risk factors are discussed. Implementation of nuclear waste disposal has to be based on multi-criteria decision making. Some of the major aspects of the issues are analyzed and described briefly to build a perception of the ethical implications and risks involved. This brief account on state of the nuclear waste disposal problems would be helpful for researchers working on radioactivity containment and disposal.